A new device for simultaneous manipulation of an endoscope and a treatment device during procedures: an ex vivo animal study - Kikuchi, Daisuke; Yamada, Akihiro; Iizuka, Toshiro; Nomura, Kosuke; Kuribayashi, Yasutaka; Kimura, Ryusuke; Yamashita, Satoshi; Furuhata, Tsukasa; Matsui, Akira; Mitani, Toshifumi; Ogawa, Osamu; Hoteya, Shu; Yahagi, Naohisa; Kaise, Mitsuru (Endoscopy, 2014)
Background and study aims: Endoscopists must maneuver both endoscope and treatment device during procedures, requiring them to release their hand from the scope to manipulate the treatment device. Aiming to improve this situation, we developed a new device called the Thumb Drive.Patients and methods: The Thumb Drive comprises a controller and catheter. After attaching the controller to the endoscope’s grip, the catheter is inserted into the forceps channel. The treatment device is then inserted into the Thumb Drive and fixed with its tip protruding from the endoscope tip. A single endoscopist resected 10 lesions in a porcine stomach by endoscopic submucosal dissection (ESD) using the Thumb Drive.Results: All lesions were resected en bloc using this new device without any perforations. The mean incision, dissection, and operative times were 97.2 ± 48.7 seconds, 121.6 ± 53.6 seconds, and 218.8 ± 67.8 seconds, respectively. Conclusions: The Thumb Drive enables the endoscopist to manipulate the treatment device with the thumb while handling the endoscope with the right hand during ESD. Its utility should be examined in in vivo studies as a next step.